Q. 1 B5.0( 1 Vote )

Find gof and fog when f: R R and g: R R is defined by

f(x) = 2x + x2 and g(x) = x3

Answer :

Since, f:R R and g:R R


fog:R R and gof:R R


f(x) = 2x + x2 and g(x)=x3


Now, gof(x) = g(f (x)) =g(2x + x2)


gof (x)=(2x + x2)3 = x6 + 8x3 + 6x5 + 12x4


and fog(x)=f(g(x))= f(x3)


fog(x) = 2x3 + x6


So, gof(x) = x6 + 6x5 + 12x4 + 8x3 and fog(x) = 2x3 + x6


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Functions - 01Functions - 01Functions - 0152 mins
Functions - 10Functions - 10Functions - 1047 mins
Functions - 05Functions - 05Functions - 0558 mins
Functions - 07Functions - 07Functions - 0748 mins
Functions - 02Functions - 02Functions - 0253 mins
Functions - 03Functions - 03Functions - 0361 mins
Functions - 08Functions - 08Functions - 0840 mins
Functions - 12Functions - 12Functions - 1252 mins
Functions - 04Functions - 04Functions - 0460 mins
Functions - 09Functions - 09Functions - 0947 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses